Do Founding Entrepreneurs Take a Causal Approach to Organizational Structure and Culture? - Cannon, Katherine (2017)
This dissertation explores the approach that entrepreneurs take towards their organizational structure and culture. As such, the underlying research question is: Do founding entrepreneurs take a causal approach to organizational structure and culture? In order to investigate this, existing literature on entrepreneurship, organizational structure and organizational culture have been critically analyzed. Although there is considerable research on entrepreneurship independently of organizational structure and culture, however the approach entrepreneurs take towards these organizational phenomena has rarely been considered. This dissertation follows a qualitative ethnographic, interpretivist methodology, using semi-structured interviews, document analysis and participant observation. The Blue Water Elite Swim Training (BEST) Centre is used as the basis of the study. According to the research presented in the literature review, as well as the evidence discovered through the aforementioned methods, it has been found that entrepreneurs use a combination of both effectual and causal approaches to their organizational structure and culture, with an element of evolution over time. The overriding limitation to this study however, is that the BEST Centre is a small organization, with seven permanent employees. This therefore makes it difficult to generalize the results presented in this dissertation, to large organizations. This dissertation concludes by considering the implications of the findings, suggesting that similar studies on whether founding entrepreneurs of larger organizations, as well as organizations in a variety of industries, are consistent in either their causal or effectual approaches to organizational structure and culture.